Green Product Innovation and Event Marketing Attributes as Drivers of B2B Brand Positioning: Evidence from Indonesia’s Heavy Equipment Industry - Shannon Abigail Mongi; Kadek Jemmy Waciko; Rifqi Nurfakhrurozi (Journal of Social Work and Science Education, 2027)
This study aims to examine the partial and simultaneous effects of Green Product Innovation and Event Marketing Attributes on the B2B Brand Positioning of PT United Tractors in Indonesia’s heavy equipment industry. A descriptive quantitative approach was employed using a purposive sampling technique involving 131 mining industry professionals and exhibition visitors at Mining Expo 2025. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Green Product Innovation has a positive and significant effect on Brand Positioning (β = 0.451; t = 4.379; p < 0.001), while Event Marketing Attributes also positively and significantly influence Brand Positioning (β = 0.397; t = 4.221; p < 0.001). Together, both variables explain 63.0% of the variance in Brand Positioning (R² = 0.630). The novelty of this study lies in extending Signaling Theory by integrating Green Product Innovation and Event Marketing Attributes to explain B2B brand positioning in Indonesia’s heavy equipment industry, a context that has received limited empirical attention. Practically, the findings suggest that heavy equipment companies should integrate sustainable product innovation with experiential exhibition strategies to strengthen market credibility and competitive positioning. This study contributes to the B2B and green marketing literature by providing empirical evidence that sustainable technological innovation and experiential event marketing jointly enhance brand positioning in industrial markets.